2005
DOI: 10.1016/j.exger.2005.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Changes in renal hemodynamics and structure in the aging kidney; sexual dimorphism and the nitric oxide system

Abstract: With advancing age the kidney shows both functional declines (falls in GFR) and development of structural damage. In most individuals this occurs slowly and does not lead to severe renal impairment unless additional insults are superimposed. There is a pronounced sexual dimorphism with females protected, due both to beneficial effects of the estrogens and damaging effects of androgens, some of which act directly on the glomerular mesangial cell to regulate growth and extracellular matrix production. Nitric oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
58
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 53 publications
0
58
1
1
Order By: Relevance
“…Although clearly speculative, the greater glomeruli number by body weight in control females may partly explain why kidney function is more preserved in females than in males during aging. 22 The higher degree of glomerulosclerosis found in our treated males as compared with females may be explained by the fact that SNGFR needs to increase more in males than in females trying to maintain GFR. The increment in SNGFR when nephron number decreases may be secondary to an elevation in glomerular capillary pressure.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Although clearly speculative, the greater glomeruli number by body weight in control females may partly explain why kidney function is more preserved in females than in males during aging. 22 The higher degree of glomerulosclerosis found in our treated males as compared with females may be explained by the fact that SNGFR needs to increase more in males than in females trying to maintain GFR. The increment in SNGFR when nephron number decreases may be secondary to an elevation in glomerular capillary pressure.…”
Section: Discussionmentioning
confidence: 88%
“…The greater glomerulosclerosis in males may also be attributed to the effects of androgens and to the absence of estrogens. 22,23 Tubulointerstitial damage found in the ARA-treated rats was expected, because it is well established that blockade of RAS during nephrogenesis results in tubular dilatation, chronic interstitial inflammation, and fibrosis in the adulthood 9 and that tubular dilatation is an early event followed by a secondary inflammatory response. 24 It is clear that tubulointerstitial injury in the renal cortex and renal medulla was also greater in males than in females, with a similar decrease in nephron number.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] In support of these possibilities, it has been shown that the sexual differences in renal damage may be explained by an decline in NO in aged male but not in aged female rats, 24 by the damaging influence of androgens in males, and/or the protective effects of estrogens. [23][24][25] The hypothesis that angiotensin II may be involved in the observed renal damage during aging is based on studies demonstrating the following: (1) the renin-angiotensin activity is enhanced in several experimental models with a reduced nephron endowment 15,26 ; (2) angiotensin II is a potent growth factor 27 ; and (3) angiotensin II effects are enhanced in the presence of androgens but reduced when estrogens are elevated. 24 In summary, the current study emphasizes the importance of COX2-derived metabolites in the regulation of nephrogenesis.…”
Section: Discussionmentioning
confidence: 94%
“…[23][24][25] The hypothesis that angiotensin II may be involved in the observed renal damage during aging is based on studies demonstrating the following: (1) the renin-angiotensin activity is enhanced in several experimental models with a reduced nephron endowment 15,26 ; (2) angiotensin II is a potent growth factor 27 ; and (3) angiotensin II effects are enhanced in the presence of androgens but reduced when estrogens are elevated. 24 In summary, the current study emphasizes the importance of COX2-derived metabolites in the regulation of nephrogenesis. We have reported new evidence showing that a slight impairment of renal development may lead to a significant increment in arterial pressure and to a sex-dependent accelerated deterioration of the renal structure and renal function.…”
Section: Discussionmentioning
confidence: 99%
“…In the aged kidney progressive glomerulosclerosis, reduced glomerular filtration rate, and vascular hyalinization all occur concomitantly with the loss of functioning nephrons (18), so that elderly kidneys are more susceptible to failure when other insults are superimposed.…”
Section: Discussionmentioning
confidence: 99%